Systematic review of Chinese medicine for the treatment of atherosclerosis - Tang, Cuiyao; Liu, Bo; Zhang, Ying; Long, Mengyang; Zheng, Wei; Lu, Jing; Li, Han; Xu, Zihui; Wang, Yunqiao (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtherosclerosis (AS) is a chronic inflammatory metabolic disease strongly associated with risk factors, including hypertension, hyperlipidemia, hyperglycemia, and hyperuricemia. AS serves as the pathological foundation for numerous cardiovascular diseases (CVDs), and it remains a major threat to global health. However, the underlying mechanisms driving AS development are incompletely understood. Elucidating the pathogenesis and key influencing factors of AS is critical for identifying novel preventive strategies and therapeutic approaches.MethodsWe searched PubMed and Web of Science for relevant studies. We selected relevant English research articles published between 2012 and 2024. Afterward,we analyzed and summarized the pharmacological effects and molecular mechanisms of these Chinese medicines.ResultsThrough our search and exclusion criteria, a total of 116 preclinical studies and 6 clinical research articles were found.DiscussionTraditional Chinese medicine (TCM), with over 2000 years of clinical application, offers a rich source of potential interventions. Integrating modern medical technologies allows for the reevaluation of TCM from a natural compound perspective. This review comprehensively summarizes the mechanisms by which single herbal medicines (SHMs) and their derived natural compounds (NCs) exert effects against AS on the basis of preclinical evidence and analysis of seven selected double-blind, randomized, placebo-controlled clinical trials (RCTs).